TaNAC020 homoeologous genes are associated with higher thousand kernel weight and kernel length in Chinese wheat - Majeed, Uzma; Hou, Jian; Hao, Chenyang; Zhang, Xueyong (Frontiers in Genetics, 2022)
NAC proteins constitute one of the largest plant specific transcription factor (TF) families and play significant roles in plant growth and development. In the present study, three TaNAC020 homoeologous genes located on chromosome 7A, 7B and 7D were isolated from wheat (Triticum aestivum L.). TaNAC020s were predominantly expressed in developing grains. The developed transgenic rice lines for TaNAC020-B showed higher starch density and lower amylose contents compared with wild type (WT). Sequence polymorphism studies showed seven and eight SNPs in TaNAC020-A/B making three and two haplotypes, respectively. No sequence polymorphism was identified in TaNAC020-D. Association analysis revealed that HAP-2 of TaNAC020-A and TaNAC020-B were favored haplotypes for higher thousand kernel weight and kernel length. Geographic distribution and allelic frequency showed that our favored haplotypes experienced strong selection in China and likewise diversity increased in TaNAC020s during wheat polyploidization. The results obtained in this study demonstrated that TaNAC020s positively influence starch synthesis and accumulation and are one of the key regulators of kernel (seed) size and kernel number and have potential for utilization in wheat breeding to improve grain yield. Molecular markers developed in this study stands instrumental in marker assisted selection for genetic improvement and germplasm enhancement in wheat.